2017
DOI: 10.1590/1980-5373-mr-2015-0611
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Erosion-oxidation Resistance of Thermally Sprayed Nanostructured Cr3C2-25(Ni-20Cr) Coatings

Abstract: This study reports the high temperature erosion-oxidation (E-O) behavior of conventional and nanostructured Cr 3 C 2 -25(Ni-20Cr) coatings prepared by high velocity oxygen fuel (HVOF) spraying. As-received and nanostructured Cr 3 C 2 -25(Ni-20Cr) powders with mean crystallite sizes of 145 nm and 50 nm respectively, were used to prepare 120 -200 μm thick coatings on AISI 310 samples. The E-O behavior of the coatings prepared with the as-received (AR) and nanostructured (NS) powders was determined as weight chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 63 publications
4
6
0
Order By: Relevance
“…The Taguchi method is a tool used to optimize various processes in industry [19][20][21], including cold spraying [22][23][24]. In this paper, we experimented using the base powder Cr 3 C 2 -25(Ni20Cr), which has been used for many years to deposit wear-resistant coatings, mainly via HVOF spraying [25][26][27]. Several studies have also been carried out on the properties of these coatings deposited by means of cold spraying [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The Taguchi method is a tool used to optimize various processes in industry [19][20][21], including cold spraying [22][23][24]. In this paper, we experimented using the base powder Cr 3 C 2 -25(Ni20Cr), which has been used for many years to deposit wear-resistant coatings, mainly via HVOF spraying [25][26][27]. Several studies have also been carried out on the properties of these coatings deposited by means of cold spraying [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be assumed that the nanometric powder may consist of amorphous structures and crystal dispersions. The XRD analysis ( Figure 2 ) explains the presence of Cr 3 C 2 [13,15,20,27,29], and Cr 7 C 3 in the micrometric powder. The intensity of the peaks decreases, while they expand as a function of milling time.…”
Section: Methodsmentioning
confidence: 99%
“…Cr 3 C 2 -25 coatings have been widely used in high-temperature (850 • C) industrial applications due to their structural stability and retention of mechanical properties at higher service temperatures [22]. A variety of techniques can be used to prepare chromium carbide-based coatings, among which HVOF processes have been widely used, as they produce smooth, low-porosity, dense, and adherent coatings, without significantly altering the integrity of the carbide particles [23]. Some preliminary studies presented in the literature that focus on laser surface modification of carbide coatings are detailed in the following: Morimoto et al tested the effect of a diode laser on a cermet coating, achieving an increase in surface hardness [24]; Sun et al, using a fiber laser, tested the effect of scan speed on wear behavior and observed that the wear resistance of the optimized layer was increased by 29.76 times [25].…”
Section: Introductionmentioning
confidence: 99%